Decent Work, Meaningful Education or Potential Exploitation? The Role of Universities in Ensuring the Quality of Academic Internships in Australia, Finland and France - Hewitt, Anne; Bo, Damien; MacKay, Will; Rosin, Annika (Wolters Kluwer, 2025)
Academic internships have become a well-entrenched feature of the tertiary education landscape and are perceived to facilitate the transition into graduate employment. However, such experiences straddle the worlds of work and education, which begs the questions: should they be regulated as work, or learning, or through specific regulation and what role should universities have? This paper examines the educational and labour regulation applicable to academic internships in Australia, Finland and France and presents qualitative empirical insights examining how university staff in each jurisdiction manage academic internships in the context of local labour laws and educational regulations. It is concluded that national regulations in France regulate academic internships so as to achieve ‘meaningful education’ for participants, while in Finland the regulatory approach appears to be tailored to ensuring academic interns are engaged in ‘decent work’. In contrast, Australia’s current regulatory context appears inadequate to consistently ensure either of these outcomes, leaving academic interns at increased risk of having neither a meaningful educational experience, nor decent work, and being exploited. Universities in Australia and Finland have an increased role in guaranteeing quality internships. However, the preliminary empirical data suggests that this role may not be consistently fulfilled.